Exploring Soul, Nature, and God. A Triad in Bhagavad gita - Sumati Yadav (Perichoresis: The Theological Journal of Emanuel University, 2017)
Humans have always been and still are fascinated by the elusive phenomenon of soul and have devised various approaches to interpret it and attribute different names to it; depending on which part, which religion, which tribe and which sect of the world they belong to. Theologians to philosophers to spiritual thinkers to literary authors and critics to scientists—all seem to be researching and explaining its nature and place in the universal scheme of things. Interestingly, there is a unanimity among all, regarding the eternity and indestructibility of soul. The ancient Hindu scripture, Bhagavad Gita establishes soul (Jivatma) as a triad of Self, Nature (Prakriti: material reality) and God (Parmeshvara). The inner self is Soul which bears reflections of both, the physical nature and God. Malleable in ignorance, it identifies with the sense-perception dominated body but once realising its true nature, it is capable of governing the body and its actions. With the support mechanisms and persistence, it traverses across individual body consciousness to universal consciousness. This article strives to make a hermeneutic study of this metaphysical text; inquiring how awareness of the duality of nature; transient and permanent, triggers a gradual process of evolution, leading to a complete transformation when a soul resides within a body as a unifying factor; not for exploiting it or others or vice versa but for bringing about universal harmony.